“Elastic Hymen with A Large Inner Diameter” in Cases of Sexual Violence: Legal and Social Consequences - Yılmaz, Özlem; Aktürk, Gökhan; Dokgöz, Halis; Billgin, Nursel Gamsız; Kar, Hakan (The Bulletin of Legal Medicine, 2023)
Objective: Hymen with wide inner opening-high elasticity; due to structure and flexibility, non-lasered hymen despite penetration of erect penis or other objects. It may cause no findings in genital examination in sexual violence cases, even if other evidences points sexual assault. Methods: Data from 1.593 cases applied to Mersin University Faculty of Medicine between January 1, 2010-June 30, 2022 and underwent vaginal examination were scanned retrospectively. Results: In 136 (8.5%) cases, hymen with wide internal opening-high elasticity were detected. This variation was found in 20 (6.6%) of 300 cases aged 18 years and older, 116 (8.9%) of 1.293 cases under age 18, and youngest age was 12, the eldest was 39. Conclusion: In some conservative and/or underdeveloped societies, absence of hymen laceration during women’s first sexual intercourse, accusations with claims of “virginity (!)” in women, “impotence (!)” in men, divorces, compensation claims, cases that can result in murder can be seen. Due to legal regulations in Türkiye expect “conclusive evidence beyond any doubt”, when laceration isn’t detected in hymen, accused takes advantage of suspicion, and victim may lose rights. Detection of this hymen type depends on physician’s subjective evaluation. For standardization; we think that hymen, which has “hymen opening is 3 cm and above”, “width is narrow enough to be measured in millimeters”, “flexible until vaginal wall” is considered to be too elastic, and new devices should be developed to provide measurements objectively.